2010
DOI: 10.1074/jbc.m109.098376
|View full text |Cite
|
Sign up to set email alerts
|

USF and NF-E2 Cooperate to Regulate the Recruitment and Activity of RNA Polymerase II in the β-Globin Gene Locus

Abstract: The human ␤-globin gene is expressed at high levels in erythroid cells and regulated by proximal and distal cis-acting DNA elements, including promoter, enhancer, and a locus control region (LCR). Transcription complexes are recruited not only to the globin gene promoters but also to the LCR. Previous studies have implicated the ubiquitously expressed transcription factor USF and the tissue-restricted activator NF-E2 in the recruitment of transcription complexes to the ␤-globin gene locus. Here we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 70 publications
6
46
0
Order By: Relevance
“…S6). Other examples of tethered binding include SP1 tethering to HNF4 in HepG2 cells and STAT3 tethering to CEBPB in HeLa cells, both with literature support (Kardassis et al 2002;Zhou et al 2010). Novel predictions of tethering include TCF12 to FOXA and HNF4 in HepG2 cells, IRF1 to NF-Y in K562 cells, SREBF1 to RFX5 in HepG2 cells, and SIX5 to ZNF143 in GM12878 cells (Supplemental Table S3).…”
Section: Analysis Of Sites Of 119 Tfs In the Human Genomementioning
confidence: 91%
“…S6). Other examples of tethered binding include SP1 tethering to HNF4 in HepG2 cells and STAT3 tethering to CEBPB in HeLa cells, both with literature support (Kardassis et al 2002;Zhou et al 2010). Novel predictions of tethering include TCF12 to FOXA and HNF4 in HepG2 cells, IRF1 to NF-Y in K562 cells, SREBF1 to RFX5 in HepG2 cells, and SIX5 to ZNF143 in GM12878 cells (Supplemental Table S3).…”
Section: Analysis Of Sites Of 119 Tfs In the Human Genomementioning
confidence: 91%
“…Previous studies have shown that Pol II interacts with LCR HS2 and with the adult β-globin gene promoter and that the binding increases on induction of MEL cell differentiation (26)(27)(28)(29). As shown in Fig.…”
Section: Resultsmentioning
confidence: 73%
“…35 Furthermore, NF-E2 has been shown to cooperate with USF1 to recruit RNA Pol II and increase expression of globin gene promoters. 36 These findings suggest a mechanism by which the ANK1E core promoter becomes activated in erythroid cells, but silent in other cell types where alternative tissue-specific ANK1 core promoters are active. We propose a model in which the expression of NF-E2 in erythroid cells allows interactions with CTCF that bring the ANK1E 3ЈHS1 enhancer and NF-E2 into juxtaposition with the GATA1-dependent ANK1E promoter.…”
Section: Discussionmentioning
confidence: 80%